“Green Movement” di Ekowisata Subak Sembung Desa Peguyangan, Kecamatan Denpasar Utara Kota Denpasar - Indra Pranata Darma, I Gusti Ketut; I Ketut Arta Widana; Ni Made Rai Kristina; I Nengah Alit Nuriawan; I Putu Suyasa Ariputra; Ida Anuraga Nirmalayani; Md Yudyantara Risadi (Sevanam: Jurnal Pengabdian Masyarakat, 2025)
This community service activity analyzes the role of the green movement in the context of Subak Sembung Peguyangan ecotourism in North Denpasar District, Denpasar City. Ecotourism has become a major focus in sustainable development in this area, with Subak Sembung Peguyangan as one of the main objectives. This research aims to understand how the green movement contributes to the development of ecotourism in the region. The research method used is a combination of field research and literature analysis. Primary data was collected through interviews with relevant stakeholders, such as tourism managers, Subak farmers, and environmental activists. Secondary data was obtained from literature related to ecotourism, environmental management, and the green movement. The results of the study show that the green movement has a significant role in the development of Subak Sembung Peguyangan ecotourism. Activities such as waste management, nature conservation, environmental education, and community participation are key in increasing awareness of the importance of environmental sustainability and local culture. In addition, the green movement also contributes to creating new economic opportunities through the establishment of sustainable businesses that involve local communities. Collaboration between the green movement and ecotourism has a positive impact on preserving the environment and culture of Subak Sembung Peguyangan. In the long term, this sustainability effort is expected to ensure that ecotourism adheres to strong sustainability principles while providing economic and social benefits to local communities